2022
DOI: 10.3390/ijms231810422
|View full text |Cite
|
Sign up to set email alerts
|

Plant Metabolic Engineering by Multigene Stacking: Synthesis of Diverse Mogrosides

Abstract: Mogrosides are a group of health-promoting natural products that extracted from Siraitia grosvenorii fruit (Luo-han-guo or monk fruit), which exhibited a promising practical application in natural sweeteners and pharmaceutical development. However, the production of mogrosides is inadequate to meet the need worldwide, and uneconomical synthetic chemistry methods are not generally recommended for structural complexity. To address this issue, an in-fusion based gene stacking strategy (IGS) for multigene stacking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…After that, Itkin et al ( 24 ) (ranked 5th in Table 3 ) identified the members of five enzyme families responsible for mogroside biosynthesis, namely the squalene epoxidases, triterpenoid synthases, epoxide hydrolases, CYP450, and UDPG. Very recently, successful mogroside biosynthesis in transgenic cucumber and tomato ( 30 ) and transgenic Nicotiana benthamiana (benth) and Arabidopsis thaliana (thale cress) ( 31 ) have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…After that, Itkin et al ( 24 ) (ranked 5th in Table 3 ) identified the members of five enzyme families responsible for mogroside biosynthesis, namely the squalene epoxidases, triterpenoid synthases, epoxide hydrolases, CYP450, and UDPG. Very recently, successful mogroside biosynthesis in transgenic cucumber and tomato ( 30 ) and transgenic Nicotiana benthamiana (benth) and Arabidopsis thaliana (thale cress) ( 31 ) have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the biosynthetic pathway of mogroside V, microbial cell factories were established by chassis cell selection and optimization, terpene synthesis-related genes of the mevalonate (MVA) pathway were overexpressed, , the expression of ERG7 was inhibited using the lanosterol synthase inhibitor R0 48-8072 or the ergosterol synthase inhibitor R0 48-8072 or by using the CRISPR/Cas9 system to down-regulate ergosterol synthesis branched pathways, , and the global upc2-1 , a mutant gene of the transcription factor UPC2, directly or indirectly upregulates the transcriptional efficiency of genes involved in the MVA pathway . Meanwhile, the cloning of related enzyme genes (SQE, CDS, EPH, CYP450, and glycosyltransferases) will provide components for heterologous expression, and heterologous expression of the enzymes will lay the foundation for functional studies. This could provide a possible strategy for the cost-effective large-scale production of SG mogroside V.…”
Section: Synthetic Biology Approaches For Sgmentioning
confidence: 99%
“…Recently, considering the high application prospects of mogrol in medicine and the low yield in extraction from plant extract, a de novo biosynthesis pathway was constructed in yeast ( Saccharomyces cerevisiae ) that can be developed as an alternate source for the production of mogrol in place its extraction from the plant [ 13 ]. Recently, a multigene stacking strategy is developed to synthesize different mogrosides through metabolic engineering in other plants [ 14 ]. Similarly, considering the role of plant-based sweeteners in the environment and economic benefits [ 15 ], researchers have created UDP-glycosyltransferase enzymes to synthesize high-intensity sweetener mogrosides from mogrol [ 16 ].…”
Section: Introductionmentioning
confidence: 99%